Cloud Technologies in Digital Education: Scaling for Global Learning - Meghana Orugunta (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores how cloud technologies are transforming digital education platforms. By examining cloud-native implementations in educational institutions, it shows how modern learning management systems have grown to handle greater scale and accessibility. The analysis looks at key architectural parts, such as microservices-based content delivery and distributed data management, highlighting their effects on system performance and user experience. It pays special attention to global scaling strategies, emphasizing how content delivery networks and elastic computing resources allow educational platforms to effectively serve diverse international audiences. The analysis also investigates how AI-driven personalization is integrated, examining how adaptive learning systems and real-time analytics improve educational results. Security considerations and compliance frameworks are analyzed, showing how educational platforms protect data while scaling globally. The analysis reveals significant improvements in system performance, cost efficiency, and learning outcomes, offering valuable insights for organizations implementing cloud-native educational platforms.